Demographic Influence On Financial Decisions In Indonesia's Chemical Industry - Veronica, Meilin (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
Decisions related to financing and investment are crucial for the sustainability and progress of businesses in the chemical goods industry. Various internal and external factors influence these decisions, one of which is the demographic category of corporate decision makers, such as gender, age, and education. The purpose of this study is to determine how the gender, age, and education level of CEOs impact financing and investment decisions in Indonesia's chemical goods industry. Quantitative methods and secondary data were used in this study, with the research sample selected using purposive sampling. The subjects of the study were 21 chemical industry companies listed on the Indonesia Stock Exchange. This study utilized a multiple linear regression model. The results of the study indicate that the age variable influences funding decisions but does not influence investment decisions, while the gender and education variables do not influence either funding or investment decisions.